The effect of the color of LED lights on some blood indicators and the level of health status for the broiler - جمول عادل; العيسى بشرى; محمد جعفر (Latakia University Journal -Biological Sciences Series, 2020)
To verify the importance of applying a modern light system of high-energy LED LEDs, which are energy-efficient, which provides comfort to the bird’s retina, and to assess their effect on some blood indicators, the level of health of the broilers, and to determine the most appropriate lighting color that enhances the calm and well-being of birds, A study was conducted on 300 broiler chickens (ROSS) in one of the private poultry in Al-Haffa area of ​​Lattakia governorate. The chicks were randomly distributed at the age of one day within five different treatments according to the LED color used (green G, blue B, mix of blue and green B+G, white W, yellow Y) And by 60 chicks per transaction, and combine One treatment three replicates of 20 thieves to duplicate one, and all the conditions of shelter, care, nutrition, and one for all transactions. The results showed a significant increase in the red blood cell count in the blood of TMIX (2,92), (2,87) TB and TG (2,77) coefficients compared to the two treatments (TW (2,61) and TY (2,56). The results also indicated a significant increase in the leukocyte count in the treatment birds TY (26,86) TW (26,96), while it was close to the three treatment birds (TG, TMIX, TB) and there were no significant differences (0,05 <P), The results of measuring glucose concentration in the blood of birds also revealed a significant increase in the concentration of glucose in the serum of the two treatment birds (192,66) TY mg / 100 ml blood and (188,66) TW mg / 100 ml blood compared to other treatments, )187,33) TG mg / 100 ml blood, (170,33) TB mg / 100 ml blood , (173,33) TMIX mg / 100 ml blood . The results of the experiment indicated that caring for birds under colored lighting has improved the health of the broilers, as the results of birds bred under the blue lighting mixture with green outperformed the rest of the other treatments.